Upper and Lower Near $(τ_1,τ_2)$-continuity (European Journal of Pure and Applied Mathematics, 2025)
This paper presents new classes of multifunctions called upper nearly $(τ_1,τ_2)$-continuousmultifunctions and lower nearly $(τ_1,τ_2)$-continuous multifunctions. Furthermore, some characterizations of upper nearly $(τ_1,τ_2)$-continuous multifunctions and lower nearly $(τ_1,τ_2)$-continuous multifunctions are established.
Keywords: upper nearly $(τ_1,τ_2)$-continuous multifunction; lower nearly $(τ_1,τ_2)$-continuous multifunction